Hoping for the best while preparing for the worst in the face of uncertainty: A new typemof incomplete preferences - Pierre Bardier; Bach Dong Xuan; Van-Quy Nguyen (Bielefeld University, Center for Mathematical Economics (IMW), 2025)
We propose and axiomatize a new model of incomplete preferences under uncertainty, which we call hope-and-prepare preferences. An act is considered more desirable than another when, and only when, both an optimistic evaluation, computed as the welfare level attained in a best-case scenario, and a pessimistic one, computed as the welfare level attained in a worst-case scenario, rank the former above the latter. Our comparison criterion involves multiple priors, as best and worst cases are determined among sets of probability distributions. We make the case that, compared to existing incomplete criteria under ambiguity, hope-and-prepare preferences address the trade-off between conviction and decisiveness in a new way, which is more favorable to decisiveness.
urn:nbn:de:0070-pub-30009222
Keywords: D01; D81; D90; 330; Decision theory; Incomplete preference; Multiple-selves; Non-obvious manipulability